The New (and Smaller) World of Higher Education - Eckel, Peter; Green, Madeleine; Barblan, Andris (International Higher Education, 2015)
During the last decade, technology, globalization, and competition have caused the ground to shift under higher education, defying national borders and calling into question honored traditions and long-held assumptions—creating a brave new world for higher education.